Spectrophotometric Determination of Pramiexole Dihydrochloride Monohydrate - SRINU BABU, G.; A.I. RAJU, CH. (Asian Journal of Chemistry, 2010)
A simple, sensitive, spectrophotometric method in UV region has been developed for the determination of pramipexole in bulk and tablet dosage form. Pramipexole is a new antipsychotic drug, which shows maximum absorbance at 261 nm with apparent molar absorptivity of 5.37208 x 103 L/mol cm. Beer's law was obeyed in the concentration range of 4-60 μg/mL. Results of the analysis were validated statistically and by recovery studies.